Current Understanding on the Heterogenous Expression of Plastic Depolymerising Enzymes in Pichia pastoris - Shuyan Wu; David Hooks; Gale Brightwell (Bioengineering)
Enzymatic depolymerisation is increasingly recognised as a reliable and environmentally friendly method. The development of this technology hinges on the availability of high-quality enzymes and associated bioreaction systems for upscaling biodegradation. Microbial heterologous expression systems have been studied for meeting this demand. Among these systems, the Pichia pastoris expression system has emerged as a widely used platform for producing secreted heterologous proteins. This article provides an overview of studies involving the recombinant expression of polymer-degrading enzymes using the P. pastoris expression system. Research on P. pastoris expression of interested enzymes with depolymerising ability, including cutinase, lipase, and laccase, are highlighted in the review. The key factors influencing the heterologous expression of polymer-degrading enzymes in P. pastoris are discussed, shedding light on the challenges and opportunities in the development of depolymerising biocatalysts through the P. pastoris expression system.